PERAN COLLECTIVE EFFICACY PADA TIM ELIT CABANG OLAHRAGA BEREGU - Lucky Abrorry; Jainuddin (Almustofa Journal of Islamic Studies and Research, 2025)
Beach volleyball is a team sport that has outstanding achievements for Indonesia in the eyes of the world, this study aims to explore collective resources commonly used by elite athletes, the informants in this study were coaches and athletes of the Indonesian men's beach volleyball national training preparations for Asia The 2023 China Games and the 2024 Paris pre-Olympics, consisting of a head coach and three athletes. Using qualitative methods by conducting in-depth observations and interviews. The results of this study conclude that the sources of collective efficacy in Indonesian beach volleyball national training athletes include individuals, teams, and the relationship between athletes and their environment; sources from individuals in the form of self talk, task efficacy, role efficacy, athlete mindset in perceiving the training process, matches, playing partners, and match results. Sources from the team are related to interactions between pairs of players, verbal and non-verbal communication patterns inside and outside the game, the role of the coach during the training process, during the match and after the match. The source of this relationship and environment is related to the presence of a person or group that is considered significant by the athlete, such as the support of his wife or children.